Evaluating the relationship between quadriceps muscle quality captured using ultrasound with clinical severity in women with knee osteoarthritis. (December 2020) - Chopp-Hurley, Jaclyn N.; Wiebenga, Emily G.; Bulbrook, Brittany D.; Keir, Peter J.; Maly, Monica R.
Abstract: Background: Infiltration of muscle with non-lean tissue, such as fat, reduces muscle quality. Ultrasound captures muscle quality through measurement of echogenicity. Given the potential implications of quadriceps muscle quality on physical function, particularly in knee osteoarthritis, the purpose of this study was to investigate the relationship between echogenicity, muscle thickness and subcutaneous fat thickness with the clinical severity of osteoarthritis. Methods: Thirty-one women with clinical knee osteoarthritis participated. Rectus femoris and vastus lateralis echogenicity, muscle thickness and subcutaneous fat thickness were measured from ultrasound images of the most symptomatic knee. Clinical severity of osteoarthritis was characterized with pain, self-reported function, six-minute walk test, and knee extensor strength. Correlation coefficients were calculated between muscle and fat architecture outcomes (muscle quality, muscle and fat thicknesses) and osteoarthritis clinical severity outcomes. Findings: Data from 25 women were of sufficient quality for analysis. Echogenicity (muscle quality) related to the six-minute walk test for both rectus femoris ( r  = −0.52, p  = 0.02) and vastus lateralis ( r  = −0.74, p  = 0.004), with poorer muscle quality related to lower mobility. Subcutaneous fat thickness was related to the six-minute walk test (rectus femoris, r  = −0.61, p  = 0.0012; vastus lateralis, r  = −0.73, p  = 0.003) and strength (rectus femoris, r  = −0.46, p  = 0.02; vastus lateralis, r  = −0.59, p  = 0.03). Muscle thickness was not related to any severity outcomes. Interpretation: Muscle quality, rather than thickness, is associated with mobility performance in women with knee osteoarthritis. Thus, interventions for osteoarthritis that specifically target muscle quality, rather than size, should be explored. Highlights: Quadriceps muscle quality was related to mobility in knee osteoarthritis. Muscle fattiness, rather than size, is potentially more important in osteoarthritis. Muscle quality may be captured using ultrasound-measured echogenicity.